STUDI IMPLEMENTASI AKUNTANSI PRODUK EMAS MENURUT PSAK 107 DAN 102 PADA PT BANK SYARIAH MANDIRI TBK CABANG JEMBER - Hisamuddin, Nur; Priatmono, Agung Budi (Universitas Islam Negeri Sunan Kudus, 2016)
This research aims to know the implementation of accountinggold products at PT Bank Syariah Mandiri Tbk Branch Jemberthat BSM gadai emas and BSM cicil emas based on PSAK 107and 102. This research is a descriptive qualitative research, amethod that is done is to interpret and said data concernedwith the current situation, attitudes, and opinions that occur inthe community, conflict two states / more, the relationshipbetween the variables, the difference between fact, the effect ofthe condition, and others. Data processing method usinginterviews and accompanied with documents related to thevalidity of the data that is triangulation. The results showedthat the accounting treatment that contains the recognition,measurement, presentation and recognition of BSM gadaiemas products are in accordance with PSAK 107 and BSM cicilemas products are already in accordance with PSAK 102.